Teacher Educators’ Foreign Language Anxiety in Face-To-Face and Online Modes - Bicjutko, Tatjana; Odiņa, Indra (Baltic Journal of English Language, Literature and Culture, 2024)
The internationalisation of universities and the ensuing policies mandating English as a medium of instruction made European universities impose corresponding requirements demanding a certain level of English language proficiency from their academic staff. Similarly, university-based teacher educators became subject to specific foreign language demands. This research focuses on university-based teacher educators who have been actively taking part in enhancing their academic English. The COVID-19 pandemic made for a prompt shift from face-to-face to online learning, providing for a comparison between the two learning environments. Since affective factors, including learning anxiety, may impact the success of language acquisition, the study addresses foreign language anxiety experienced by teacher educators when acquiring English for Academic Purposes in different learning modes. The research was conducted as a survey with the data obtained through administering the adapted Foreign Language Classroom Anxiety Scale to 80 respondents from the 7 universities working in teacher education, furthered by 4 online semi-structured interviews. The findings reveal overall low levels of anxiety, with a small increase in communication apprehension. Although there is no conclusive evidence about the decrease in anxiety in remote studies, the interview results are clearly demonstrative of the possibility of combining face-to-face and online learning modes.